التناص وجمالياته في رواية روزا لهند جودر - ساسية باسي; نور مسعي عون; منى برتيمة (University of El-Oued جامعة الوادي, 2025)
الملخص: تطرقنا فيهذا الموضوع إلى أشكال التناص وجمالياته في رواية روزا لهند جودر، حيث وجدنا أن هذا المتن الروائي حافل بأشكال تناصية مختلفة المصادر،حيث تم تقسيم العمل إلى فصلين مسبوقين بمقدمة وتمهيد، حيث جاء التمهيد عرضا لمفهوم التناص وتطوره عند الغرب والعرب، أما الفصل الأول فتناولناالتناص التاريخي والديني، أما الثاني جاء لإبراز أنواع النصوص الأدبية والدينية الغائبة واستنطاقها واستقراء دلالتها، وأنهينا العرض بخاتمة تطرقنا فيها إلى أهم النتائج التي توصلنا إليها. Résumé :فرنسية أو انجلزية We tackled in this study the forms and aesthetics of intertextuality in the novel Rosa by Hind Judur، where we found that this narrative text is rich in various forms of intertextuality stemming from diverse sources. The work was divided into two chapters، preceded by an introduction and a preface. The preface presented the concept of intertextuality and its development in both Western and Arab contexts. The first chapter focused on historical and religious intertextuality، while the second aimed to highlight the types of absent literary and religious texts، giving them voice and exploring their meanings. We concluded the study with a final section summarizing the key findings we reached..
مذكرة .ماستر . أدب حديث ومعاصر. 2025
Keywords: التناص – رواية روزا – آليات التناص; Intertextuality – Rosa's novel – Mechanism of Intertextuality